Characteristics of Egg Production and Discovery of the Prolactin Gene in Indigenous Tropical White Leghorn Layer Chickens of Indonesia - N Pratiwi; T Sartika; Komarudin; T Haryati; T Kostaman; N Azizah; A Sukmara; B Brahmantiyo; Isbandi; H Zaenal; H Nuraini; H Khasanah; et al. (Brazilian Journal of Poultry Science)
ABSTRACT White Leghorn/WL chicken was imported to Indonesia in 2007. However, suboptimal production ensued due to inadequate maintenance management. This research aims to evaluate the egg production traits of WL chickens at the IRIAP (Indonesian Research Institute for Animal Production). A total of 185 WL chickens (5 batches) were utilized, with 47 DNA samples sequenced using specific primers for the PRL gene’s exons 2 and 5. Various parameters were observed, including age at first laying (AFL), body weight at first laying (BWFL), egg weight at first laying (EWFL), total egg numbers (TEN), hen-day egg production (HEP), average egg weight (AEW), feed consumption (FC), feed conversion ratio (FCR), and mortality. The findings indicated that AFL, BWFL, and EWFL did not display significant differences across all batch groups (p>0.05). TEN differed significantly between WL chickens at 24 weeks in B2 and B3 compared to B4 and B5 (p<0.05). The HEP of WL chickens exhibited a steady increase weekly, reaching a production peak of 96.2% at 28 weeks. The highest AEW observed between 41-44 weeks was 54.71 g, with FC and FCR recorded at 102 g and 2.11 respectively. Mortality throughout the 24 weeks was 5.41%. A single nucleotide polymorphism (SNP) was identified in intron 4 at g.7883 C>T (AF288765), with AH013783.3 (WL) showing the allele C, albeit in a monomorphic state. In conclusion, the productivity of WL chickens demonstrates favorable performance. Further investigation with a larger population is necessary to explore SNPs in the PRL gene thoroughly.